2015
DOI: 10.1038/ncomms8414
|View full text |Cite|
|
Sign up to set email alerts
|

Delivery of crop pollination services is an insufficient argument for wild pollinator conservation

Abstract: There is compelling evidence that more diverse ecosystems deliver greater benefits to people, and these ecosystem services have become a key argument for biodiversity conservation. However, it is unclear how much biodiversity is needed to deliver ecosystem services in a cost-effective way. Here we show that, while the contribution of wild bees to crop production is significant, service delivery is restricted to a limited subset of all known bee species. Across crops, years and biogeographical regions, crop-vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
650
7
17

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 770 publications
(727 citation statements)
references
References 56 publications
28
650
7
17
Order By: Relevance
“…These results emphasize that the conservation system that targets each specific species is vital since conserving only the ecosystem at large scale may not be adequate to support the conservation of the rare/threatened species in the system [7,39]. This notion could also work for other mobile organisms such as, bird and insect pollinator communities in which the conservation of ecosystem as a system would also consider the rare/threatened species [40,41]. In general, our study indicates the importance of exploring the species composition in relation to the spatial and environmental gradients to identify the appropriate conservation approach and correspondingly set conservation priority that fits to each site and species characteristics in Acacia-Commiphora woodland ecosystem.…”
Section: Discussionmentioning
confidence: 89%
“…These results emphasize that the conservation system that targets each specific species is vital since conserving only the ecosystem at large scale may not be adequate to support the conservation of the rare/threatened species in the system [7,39]. This notion could also work for other mobile organisms such as, bird and insect pollinator communities in which the conservation of ecosystem as a system would also consider the rare/threatened species [40,41]. In general, our study indicates the importance of exploring the species composition in relation to the spatial and environmental gradients to identify the appropriate conservation approach and correspondingly set conservation priority that fits to each site and species characteristics in Acacia-Commiphora woodland ecosystem.…”
Section: Discussionmentioning
confidence: 89%
“…Klein et al (2007) pointed to nine pollinator-dependent crops that did not exhibit proof of honeybee presence, and that three of these (atemoya, passion fruit, and vanilla) are now hand-pollinated in parts of the world, due in part to the reduced presence of the relevant wild pollinators. Kleijn et al (2015) showed that 80% of crop pollination across five continents is carried out by just 2% of all wild bee species in the areas they studied and contribute the vast majority of economic returns in agricultural systems. Besides ethical reasons, the authors argued that there are other important reasons for conserving other wild bees that do not pollinate crops and offer little economic return to farmers.…”
Section: Impacts On Pollination Servicesmentioning
confidence: 99%
“…Wild bees are also vital, and often better than Apis, as crop pollinators, with the importance of honeybees often over-emphasised in the past (see Breeze et al 2011;Garibaldi et al 2013). For example, halictid bees are important for melon (Rodrigo-Gomez et al 2016) and watermelon (Garantonakis et al 2016), bumblebees are important for blueberries (Button and Elle 2014) and several wild bees are better than managed honeybees at pollinating apples (Mallinger and Gratton 2015), although it is only a few relatively common solitary bee species that are crucial across crops in general (Kleijn et al 2015). Table 5 Heterospecific deposition by different groups of bees and non-bees for all plant species pooled, at each study site.…”
Section: Discussionmentioning
confidence: 99%